Aspectos de la biologia de Cycloneda limbifer Casey (Coleoptera: Coccinelidae) - Castro Mata, O.=700 1 Morales Dominguez, B.; Martinez Rodrriguez, J.; Gonzalez Gonzalez, A.; Grande, J.; Aguiar Herrera, L.
(En, Es)
ilus., 4 ref.
Keywords: COLEOPTERA; COCCINELLIDAE; BIOLOGIA; CUBA; CYCLONEDA LIMBIFER